Med Int 2021
DOI: 10.3892/mi.2021.3
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of taurine against diabetes and renal‑associated disorders (Review)

Abstract: To develop novel therapeutic methods for both diabetic and renal disorders, scientists had initially focused on elucidating the molecular mechanisms of taurine in established cell lines and mouse models. Although a large amount of data have been revealed, taurine has been confirmed to be the next step of novel promising therapeutic interventions against diabetic disorders. Taurine appears to ameliorate diabetes 1-related complications in various organs through its antioxidant, anti-inflammatory and anti-hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 209 publications
(344 reference statements)
0
6
0
1
Order By: Relevance
“…Studies have also emphasized the preventive and therapeutic effects of taurine therapy on the central nervous system (stroke, neurodegenerative diseases such as AD, Huntington, and Parkinson’s disease, epilepsy, and retinal degeneration), cardiovascular system (congestive heart failure, hypertension, atherosclerosis, ischemia–reperfusion injury, myocardial arrhythmias, metabolic diseases including mitochondrial diseases, diabetes, and arthritis), and muscles (sarcopenia, Duchenne muscular dystrophy, and myotonic dystrophy)[ 121 ]. Moreover, several studies have reported the beneficial effects of taurine on the kidney tissue in diabetic nephropathy, Fanconi anemia, cystinosis, chronic kidney disease, and acute kidney injury caused by lead, arsenic, acetaminophen, gentamycin, and radiation [ 122 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also emphasized the preventive and therapeutic effects of taurine therapy on the central nervous system (stroke, neurodegenerative diseases such as AD, Huntington, and Parkinson’s disease, epilepsy, and retinal degeneration), cardiovascular system (congestive heart failure, hypertension, atherosclerosis, ischemia–reperfusion injury, myocardial arrhythmias, metabolic diseases including mitochondrial diseases, diabetes, and arthritis), and muscles (sarcopenia, Duchenne muscular dystrophy, and myotonic dystrophy)[ 121 ]. Moreover, several studies have reported the beneficial effects of taurine on the kidney tissue in diabetic nephropathy, Fanconi anemia, cystinosis, chronic kidney disease, and acute kidney injury caused by lead, arsenic, acetaminophen, gentamycin, and radiation [ 122 ].…”
Section: Methodsmentioning
confidence: 99%
“…( 49 ) showed that conjugated bile acid levels were positively associated with an increased risk of diabetes. It is worth noting that the level of taurine decreased in bile metabolism, a substance currently known to be beneficial in diabetic nephropathy, which has significant antioxidant properties, improves diabetic insulin resistance, reduces the oxidative stress state produced by stimulation of chronically high glucose levels, and reduces comorbidities ( 50 , 51 ). In this experimental study, it was found that the levels of chenodeoxycholic acid, chenodeoxycholic acid glycine conjugate, cholic acid and glycocholic acid increased, while taurine and Taurocholic acid decreased ( Figures 12 , 13 ), suggesting that the structure of the gut microbiota in diabetic nephropathy rats affects the circulation of bile acids in the intestine, leading to stress responses and inflammation in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 presents the percentage of lymphocyte viability at different time points (24,48, and 72 hours) following treatment with varying concentrations of Taurine, up to 1 M (mol). The findings indicate that increasing the concentration of Taurine beyond 100 μM can lead to decreasing lymphocyte viability of the experimental group at both 48 and 72 hours.…”
Section: Cytotoxicity-mtt Assaymentioning
confidence: 99%